PENERAPAN PASAL 17 AYAT (2) PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN DAN PENETAPAN BATAS BIDANG BIDANG TANAH - Kurnia Purnama Sumsa (Dinamika, 2022)
ABSTRACTThe problem of land is a very basic problem in people's lives so that it often causes prolonged disputes, so the implementation of land registration, land bookkeeping, and the issuance of land documents are very important for the community. So that in this study formulate: 1. How is the application of Article 17 paragraph 2 of Government Regulation No. 24 of 1997 in Pamanto Village, Empang District, Sumbawa Regency? 2. What are the factors that hinder the application of Article 17 paragraph 2 of Government Regulation No. 24 of 1997 in Uncle Village, Empang District, Sumbawa Regency? 3. How to overcome obstacles in the application of article 17 paragraph 2 of government regulation number 21 of 1997 in the village of Uncle, sub-district of Empang, Sumbawa regency. The research method uses empirical juridical research or field research. The application of article 17 paragraph 2 of government regulation number 24 of 1997 in the village of Uncle, Empang sub-district, Sumbawa district, namely the absence of legal certainty over land, setting boundaries and difficulty in issuing land rights certificates.Key Word : application of article 17, implementation of land registration,   determination of boundaries  ABSTRAKMasalah tanah merupakan masalah yang sangat mendasar dalam kehidupan masyarakat sehingga seringkali menimbulkan sengketa yang  berkepanjangan, maka pelaksaan pendaftaran tanah, pembukuan tanah, serta pemberian surat – surat tanah sangat penting bagi masyarakat. Sehingga dalam penelitian ini merumuskan : 1. Bagaimana Penerapan paasl 17 ayat 2 Peraturan Pemerintah Nomor 24 tahun 1997 di Desa Pamanto kecamatan Empang Kabupaten Sumbawa? 2. Faktor apa saja yang menjadi penghambat dalam penerapan pasal 17 ayat 2 peraturan pemerintah nomor 24 tahun 1997 di desa pamanto kecamatan empang kabupaten sumbawa? 3. Bagaimana upaya mengatasi hambatan dalam penerapan pasal 17 ayat 2 peraturan pemerintah nomor 21 tahun 1997 di desa pamanto kecamatan empang kabupaten sumbawa. Metode penelitian menggunakan jenis penelitian yuridis empiris atau penelitian lapangan. Penerapan pasal 17 ayat 2 peraturan pemerintah nomor 24 tahun 1997 di desa pamanto kecamatan empang kabupaten sumbawa yakni tidak adanya suatu kepastian hukum tanah, penetapan batas dan susah menerbitkan sertifikat hak atas tanah.Kata Kunci : penerapan pasal 17, pelaksanaan pendaftaran tanah, penetapan batas